2014
DOI: 10.1039/c3gc42489h
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of the lignin in Phyllostachys heterocycla cv. pubescens in an ethanol solvothermal system

Abstract: The cracking of phenylpropyl side-chain C–C bonds in lignin followed the order Cα–Cβ, C1–Cα, Cβ–Cγ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 40 publications
5
84
0
Order By: Relevance
“…Less water in ethanol/H 2 O co-solvent led to lower conversion of hemicellulose. In agreement with our previous report36, the presence of ethanol in the system was beneficial to lignin dissolution. When the concentration of ethanol (CE, volume concentration of ethanol in H 2 O) increased from 0 to 0.5, the conversion of lignin increased from 27.5 to 38.6 wt%.…”
Section: Resultssupporting
confidence: 93%
“…Less water in ethanol/H 2 O co-solvent led to lower conversion of hemicellulose. In agreement with our previous report36, the presence of ethanol in the system was beneficial to lignin dissolution. When the concentration of ethanol (CE, volume concentration of ethanol in H 2 O) increased from 0 to 0.5, the conversion of lignin increased from 27.5 to 38.6 wt%.…”
Section: Resultssupporting
confidence: 93%
“…After that, the catalyst was calcined in a muffle furnace at 500 °C for 4 h. Prior to the next reaction, hydrogenation treatment would greatly increase, though its hydrogenation products were definitely detected. According to our previous investigations [38], it was found that many lignin oligomers existed in the liquid mixture, since the yield of identified monophenols was less than 10%. Therefore, we speculate that the Pd/γ-Al2O3 catalyst is favorable for the depolymerization of lignin oligomers for producing monophenols, especially 4-ethylphenol under very mild conditions.…”
Section: Recyclability Of the Catalystmentioning
confidence: 99%
“…a The yield of the monophenols from lignin-derived liquid mixture in our previous work [38]; b the yield of monophenols by the hydrogenation of the lignin-derived liquid mixture obtained in our previous work [38]; reactant (0.45 mmol), H 2 O (25 mL), 3 wt. % Pd/γ-Al 2 O 3 (0.200 g, 0.056 mmol Pd), 60˝C, 2 MPa H 2 , 12 h; reaction mixture stirred at 500 rpm; c the hydrogenation products were detected in GC-MS, but not quantified by GC due to the lack of standard substances.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations